Women Get Heart Disease Too: A Brief History of Gender Discrimination in Medical Research - Shalala, Donna E. (Columbia Journal of Gender and Law, 2000)
Thirty years ago, I got my first academic appointment as an assistant professor of political science at a well-known university. My Department Chair greeted me by announcing that he was very glad I was joining the University. But he didn’t want any misunderstanding: I would not be getting tenure. “Women do not get tenure,” he said, as if stating a rule of black letter law. So the message my Department Chair delivered was unmistakable-and typical for that time: the welcome mat is not out. But at least I knew where I stood. I soon found a better appointment and got tenure in due course. Unfortunately, for many women in the academy, and other businesses and industries, the obstacles were too high–and the resistance to change too strong. That resistance came in many forms: sometimes overt, other times silently and behind closed doors. It also came in places that even today have the power to shock. For example, most people know that for decades women were systematically excluded from medical school. Less well known, but equally insidious, is the tragedy of women being discriminated against in the delivery of health care. I’m not talking about the long history of doctors telling women: “Go home, it’s all in your head.” That sort of abuse was bad enough. But there are also examples of systemic gender discrimination–4olerated and sometimes encouraged by the very agencies of government that were responsible for protecting the women. One such agency was my own: the United States Department of Health and Human Services (HHS), which has the statutory duty to fund biomedical research and approve the development of new drugs. For many years, this was not a duty that the Department carried out with women in mind.